2020
DOI: 10.1155/2020/2380124
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of EZH2 in Non-Small-Cell Lung Cancers: A Meta-Analysis and Bioinformatics Analysis

Abstract: Background. The prognosis of non-small-cell lung cancer (NSCLC) has not been significantly improved. In the past several years, research on epigenetics is in full swing. There is a focus on the gene EZH2; however, its role as a predictor of the prognosis of NSCLC is in the debate. Objective. To clarify if the expression level of EZH2 can influence the prognosis of NSCLC and explain its prognostic value. Methods. We have systematically searched PubMed, Web of Science, and Cochrane library, screened relevant art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The expression of EZH2 was positively correlated with the expression of BRAF, especially in lung squamous cell carcinoma. High expression of EZH2 and its possible synergy with KRAS and BRAF mutations [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of EZH2 was positively correlated with the expression of BRAF, especially in lung squamous cell carcinoma. High expression of EZH2 and its possible synergy with KRAS and BRAF mutations [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of EZH2 mRNA are in full swing, and its mechanism is associated with silencing epigenetic genes [2]. Studies have shown that abnormal expression of EZH2 is associated with poor prognosis in various malignancies such as lung [3]. EZH2 regulates gene expression to prevent differentiation of stem and progenitor cells, and abnormalities in EZH2 activity are thought to be drivers of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…EZH2 was also highly expressed in the lung cancer with positive KRAS expression, exhibiting a positive correlation, as well as with the expression of BRAF, especially in lung squamous cell carcinoma. High expression of EZH2 possibly possess a synergy with KRAS and BRAF mutations 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies of EZH2 mRNA are in full swing recently, with its mechanism demonstrated to be associated with silencing epigenetic genes 3 . Studies have indicated that the abnormal expression of EZH2 is associated with poor prognosis in various malignancies such as lung 4 . EZH2 manipulates gene expression to prevent the differentiation of stem and progenitor cells, of which the abnormalities in activity are considered to be drivers of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…EZH2 has been identified as a critical downstream component of the retinoblastoma tumor suppressor protein (pRB)–E2F pathway, which is essential for cancer cell proliferation and growth [ 11 ]. EZH2 is an epigenetic regulator of cell proliferation that is overexpressed in most cancers, and high levels of EZH2 expression correlate with poor prognosis [ 12 , 13 , 14 , 15 , 16 ]. In addition, EZH2 also plays a critical role in anti-senescence programs in both non-tumor cells and tumor cells.…”
Section: Introductionmentioning
confidence: 99%